Using the Response Surface Methodology to Optimize the Extraction of Silica and Alumina from Coal Fly Ash for the Synthesis of Zeolite Na-A - Matlob A.S.; Kamarudin R.A.; Jubri Z.; Ramli Z. (2023)
Response surface methodology and inductively coupled plasma-optical emission spectroscopy were used to analyze the silicon (Si) and aluminum (Al) ion concentrations extracted from microwave-assisted hydrothermal fusion reactions between coal fly ash (CFA) and sodium hydroxide solution. The extracts containing Si and Al ions were successfully converted to zeolites by hydrothermal treatment at 95C for 72 h. Fifteen experimental conditions for the extraction process were obtained using Box-Behnken design through the manipulation of three independent variables. These variables include NaOH concentration (2, 4 and 6 M), power level of microwave irradiation (10, 50 and 100 W)+++ and exposure time (1, 3.5 and 6 min). The statistical analysis result indicated a significant interaction effect with a p value of 0.001. Increasing the values of all the three variables led to an increase in the concentration of Si and Al ions in the CFA extract. The optimized combinations of the three variables within the experimental range for Si and Al extraction were 5.6 M for NaOH concentration, 5.5 min time of exposure to microwave irradiation and 100 W of microwave power level. Based on the extracted concentration values of Si and Al, three products were isolated; zeolite Na-A, sodalite octahydrate and gibbsite which were characterized by their XRD images. Plots of percent yield of the final products versus [Si 4+] and [Al 3+] revealed a trend of the types of product for various ranges of concentrations of the ions in the extracts prior to hydrothermal treatment at 95C. 2011 King Fahd University of Petroleum and Minerals.